Update on Diagnosis and Treatment of Diabetic Retinopathy: A Consensus Guideline of the Working Group of Ocular Health (Spanish Society of Diabetes and Spanish Vitreous and Retina Society). (14th June 2017) - Corcóstegui, Borja; Durán, Santiago; González-Albarrán, María Olga; Hernández, Cristina; Ruiz-Moreno, José María; Salvador, Javier; Udaondo, Patricia; Simó, Rafael
Abstract : A group of members of the Spanish Retina and Vitreous Society (SERV) and of the Working Group of Ocular Health of the Spanish Society of Diabetes (SED) updated knowledge regarding the diagnosis and treatment of diabetic retinopathy (DR) based on recent evidence reported in the literature. A synthesis of this consensus forms the basis of the present review, which is intended to inform clinicians on current advances in the field of DR and their clinical applicability to patients with this disease. Aspects presented in this article include screening procedures of DR, new technologies in the early diagnosis of DR, control of risk factors in the different stages of the disease, indications of panretinal laser photocoagulation, efficacy of intravitreal antiangiogenic agents and steroids, and surgical options for treating DR-related complications. Practical information regarding periodicity of screening procedures in patients with type 1 and type 2 diabetes, ophthalmological controls according to the stage of retinopathy and complications, and criteria and degree of urgency for referral of a DR patient to the ophthalmologist are also presented.